2017
DOI: 10.1016/j.amjmed.2017.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Ambulation Orderly Program Among Cardiac Surgery Patients

Abstract: Background Despite the known benefits of ambulation, most hospitalized patients remain physically inactive. One possible approach to this problem is to employ Ambulation Orderlies (AOs) – employees whose main responsibility is to ambulate patients throughout the day. For this study, we examined an AO program implemented among post-cardiac surgery patients and its effect on patient outcomes. Methods We evaluated post-operative length of stay, hospital complications, discharge disposition, and 30-day readmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…Second, less than half of the approached patients consented to participate in this trial, and this may have resulted in our recruiting a healthier population that was more able to ambulated and less likely to benefit from an AO. Indeed, functional status was relatively high, our trial population’s surgical LOS was shorter than our institutional norms (at median of 6.5 days vs 7.5 days (11)), and patients walked more than 2000 steps per day, a value higher than expected for a hospitalized surgical population. (14) Third, we did not track how often the AO visited patients because we assumed that measuring ambulation (3 minute bouts of exercise) with the accelerometer would be sufficient.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Second, less than half of the approached patients consented to participate in this trial, and this may have resulted in our recruiting a healthier population that was more able to ambulated and less likely to benefit from an AO. Indeed, functional status was relatively high, our trial population’s surgical LOS was shorter than our institutional norms (at median of 6.5 days vs 7.5 days (11)), and patients walked more than 2000 steps per day, a value higher than expected for a hospitalized surgical population. (14) Third, we did not track how often the AO visited patients because we assumed that measuring ambulation (3 minute bouts of exercise) with the accelerometer would be sufficient.…”
Section: Resultsmentioning
confidence: 74%
“…Our prior research found that, the institution of our AO program was associated with 1.3 day shorter hospital length of stay and a reduced risk of falls. (11) Although these results are promising, they could have been confounded due to other institutional trends or occurred though a mechanism other than increased ambulation.…”
Section: Introductionmentioning
confidence: 89%
“…La enfermedad cardiovascular es la primera causa de morbimortalidad en Colombia y en el mundo; su tratamiento se basa en terapias farmacológicas y en fases avanzadas mediante tratamiento quirúrgico o intervencionista. Los pacientes que son sometidos a cirugía cardiaca atraviesan una serie de alteraciones que afectan sus funciones fisiológicas y las motoras y/o cognitivas, lo que conlleva a una disminución en la capacidad para desarrollar las actividades de la vida diaria, generando así, un déficit de autocuidado (21,22). Adicionalmente, la escala utilizada en este estudio es útil para medir el estado funcional de las personas cuando son dadas de alta de un servicio de cuidado intensivo (23).…”
Section: Discussionunclassified
“…[10][11][12] Furthermore, institutions with formal ambulation programs have reported enhanced adherence to ambulation protocols by patients and hospital staff. [13][14][15][16] Many guidelines regarding VTE prophylaxis include explicit recommendations stating that hospitals and surgical services should synthesize a formal VTE prophylaxis algorithm that includes a risk assessment tool and a specified regimen for VTE prevention. [17][18][19][20] Our surgical department is a member of the American College of Surgeons National Surgical Quality Improvement Program (ACS NSQIP), which releases semiannual rankings of each participating hospital and service on the basis of adverse event rates.…”
Section: Introductionmentioning
confidence: 99%